New Prostate Cancer Targets for Diagnosis, Imaging, and Therapy: Focus on Prostate-Specific Membrane Antigen - Cimadamore, Alessia; Cheng, Monica; Santoni, Matteo; Lopez-Beltran, Antonio; Battelli, Nicola; Massari, Francesco; Galosi, Andrea B.; Scarpelli, Marina; Montironi, Rodolfo (Frontiers in Oncology, 2018)
The rising incidence rate of the cancer in the prostate gland has increased the demand for improved diagnostic, imaging and therapeutic approaches. Prostate-specific membrane antigen (PSMA), characterized by folate hydrolase and carboxypeptidase activity as well as internalization function, is highly expressed in the epithelial cells of the prostate and is strongly upregulated in prostate cancer (PCa), with elevated expression correlating with androgen independence, metastasis and progression. Recently, PSMA has been an active target of investigation by several approaches, including the successful use of small molecule inhibitors, RNA aptamer conjugates, PSMA-based immunotherapy, and PSMA-targeted prodrug therapy. Future investigations of PSMA in PCa should focus in particular on its intracellular activities and functions. The objective of this contribution is to review the current role of PSMA as a marker for PCa diagnosis, imaging and therapy.